Optimize The Authority To Judicial Review By The Supreme Court - Janpatar Simamora (Scholar Center, 2023)
Determined of Supreme Court Regulation Number 1 of 2011 about the Right to Test Material, where one of the substances remove strained period the submission deadline Applications for approval were previously limited to 180 days after regulation laws and regulations determined as previously regulated in the Regulations Supreme Court Number 1 of 2004 should be welcomed as a positive step in in order to make the authority to review statutory regulations effective by Supreme Court. In the future, in order to further optimize authority Therefore, the Supreme Court Regulations Concerning the Right to Judicial Review need to be revised through the establishment of Supreme Court Regulations regarding regulatory review regulations that include the right to material review and the right to formal review, because However, the Supreme Court does not only have the authority to carry out material tests also formal testing where the two understanding authorities are better known as the term judicial review authority.